2016
DOI: 10.14260/jemds/2016/1197
|View full text |Cite
|
Sign up to set email alerts
|

Management of Ileal Perforation Using Apache – Ii Scoring: A Prospective Study

Abstract: BACKGROUNDPeritonitis resulting from small bowel perforation is a frequently encountered surgical problem in India. A review of literature indicates a very high mortality associated with this condition in spite of advances in treatment. The management of ileal perforation has been a subject of controversy. Operative treatment has been generally accepted as the treatment of choice, but the choice of procedure continues to be debated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Agrawal et al also reported that in their series of 14 women there was no case of histologically proven malignancy. 9 Mumtaz et al reported degeneration in 3 patients out of 26 patients in their series. 4 The scar integrity following CM was excellent in 93.3% cases who underwent repeat CS with us.…”
Section: Discussionmentioning
confidence: 85%
“…Agrawal et al also reported that in their series of 14 women there was no case of histologically proven malignancy. 9 Mumtaz et al reported degeneration in 3 patients out of 26 patients in their series. 4 The scar integrity following CM was excellent in 93.3% cases who underwent repeat CS with us.…”
Section: Discussionmentioning
confidence: 85%